Implementation of the Flipped Classroom to Promote Junior High School Students’ Reading Comprehension: Students’ Perceptions - Sukristiningsih Sukristiningsih (Medan Resource Center, 2025)
This study examines junior high school students’ perceptions of the flipped classroom as an instructional approach to enhancing reading comprehension in an English as a Foreign Language context. The research is grounded in concerns regarding students’ limited engagement and comprehension in conventional reading instruction, prompting an exploration of alternative pedagogical models. Employing a quantitative descriptive research design, data were collected from 30 students using a ten-item questionnaire measuring perceptions related to difficulty, motivation, accessibility, learning support, and perceived learning outcomes. The instrument was subjected to validity and reliability testing and analyzed using descriptive statistics. The findings indicate that students generally expressed positive perceptions of the flipped classroom, particularly in terms of increased learning motivation, confidence, and support for reading comprehension, despite experiencing initial adaptation challenges. The analysis further revealed that seven questionnaire items met validity criteria and the instrument demonstrated acceptable reliability for exploratory research purposes. The study argues that the flipped classroom constitutes a pedagogically viable approach for improving reading comprehension, provided that sufficient instructional guidance and technological support are systematically integrated into the learning process.